2021
DOI: 10.4103/joacp.joacp_60_19
|View full text |Cite
|
Sign up to set email alerts
|

Airway management using LMA-evaluation of three insertional techniques-a prospective randomised study

Abstract: Background and Aims: Laryngeal Mask Airway [LMA] insertion has become as a basic procedural skill needed for all health care providers. Search for the most successful insertion technique continues. We evaluated the success rate of the three LMA insertion techniques- standard, 90 degree rotational and 180 degree rotational technique. Material and Methods: A total of 180 patients of ASA I-II aged 18-65 years undergoing open superficial surgical procedures with (LMA® Uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…They assessed the success rates of standard, 90° rotational and 180° rotational techniques and reported that 180° and 90° rotation techniques were associated with better results compared to the standard method. [ 25 ] In another study by Mahmoodpoor and colleagues, they assessed the standard and two rotational methods of LMA placement in 150 adult patients undergoing anesthesia. Based on the results of this study, inserting the LMA using lateral rotation was associated with higher success rates and lower insertion time.…”
Section: Discussionmentioning
confidence: 99%
“…They assessed the success rates of standard, 90° rotational and 180° rotational techniques and reported that 180° and 90° rotation techniques were associated with better results compared to the standard method. [ 25 ] In another study by Mahmoodpoor and colleagues, they assessed the standard and two rotational methods of LMA placement in 150 adult patients undergoing anesthesia. Based on the results of this study, inserting the LMA using lateral rotation was associated with higher success rates and lower insertion time.…”
Section: Discussionmentioning
confidence: 99%
“…Shyam and Selvaraj explored 3 distinct LMA insertion methods. The first method involved the standard technique, the second method, known as the 90° rotation technique, and the third method (referred to as the 180° rotation technique) ( 12 ). The researchers concluded that the 180° rotation technique of LMA insertion is more efficacious than the 90° rotation technique in adult patients under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The third method, referred to as the 180° rotation technique, involved the insertion of the LMA from the back to the front, similar to Godel’s airway. Based on their findings, the researchers concluded that the 180° rotation technique of LMA insertion is more effective than the 90° rotation technique in adult patients under general anesthesia ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 90 • rotational technique is similar to the 180 • technique except that after the LM device with a fully deflated cuff is inserted laterally into the mouth, it is rotated counterclockwise through 90 • and advanced and straightened out in the hypopharynx. These rotational techniques have been shown to be better than the standard technique in randomized trials in children and adults during anesthesia [41][42][43]. Nevertheless, apart from the standard technique, none of these techniques have been studied in newborn infants during resuscitation.…”
Section: Insertion Technique and Trainingmentioning
confidence: 99%